Tracking extinction risk trends and patterns in a mega-diverse country: A Red List Index for birds in Colombia. - Luis Miguel Renjifo; Angela María Amaya-Villarreal; Stuart H M Butchart (PLoS ONE)
Monitoring trends in the extinction risk of species is important for tracking conservation effectiveness. The Red List index (RLI) reflects changes in aggregate extinction risk for sets of species over time (a value of zero means that all species are extinct, a value of one means that all species are categorized as Least Concern). We calculated the first national RLI for birds in Colombia for the period 2002-2016, and disaggregated indices by ecosystems, regions, and species groups. Overall, the status of birds in Colombia has moderately deteriorated during 2002-2016, declining by 0.0000714% per year (the global RLI for birds declined by 0.0297% per year). High Andean forest, paramo, and freshwater are the ecosystems in worst condition. The two regions with the greatest avian diversity contrasted: the Andes has the lowest RLI, and the Amazon the highest. Among species groups, gamebirds, parrots, large frugivores, and forest raptors are the most threatened. Habitat loss from expansion of illicit crops and population declines from hunting were the most important threats. Agricultural expansion, invasive alien animal species, illegal logging and illegal mining are significant threats for some species. Tracking species' extinction risk is important in a country with the highest bird species richness in the world, dynamic spatial patterns of habitat loss, and high levels of endemism. Recent developments provide reasons for both hope and despair. In 2016, a peace agreement ended 50 years of armed conflict. New opportunities for biodiversity conservation, local development based on bird-watching tourism, and advancement in scientific knowledge of birds now occur alongside dramatic increases in deforestation. These new conservation opportunities and challenges provide strong motivation to take advantage of the fact that the overall risk of extinction of birds in Colombia is still relatively low and stable. Effective action is urgently needed while there still is the opportunity to prevent extinctions and safeguard species, particularly those in higher risk categories.